2017
DOI: 10.1097/mjt.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Acute Asthma Exacerbation in Drug Users

Abstract: The characteristics of patients who use heroin, cocaine, or both and present with acute asthma exacerbations have not been well studied. In this retrospective study, we aimed to study the demographic characteristics of this patient population, the characteristics of their asthma attack, and the risk factors for the need for invasive mechanical ventilation in this patient population. We reviewed the charts of patients discharged from an inner-city hospital with a diagnosis of acute asthma exacerbation. Individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
6
0
6
Order By: Relevance
“…Si cette consommation est soupçonnée, une analyse toxicologique des urines pour les opiacés peut confirmer le diagnostic. Une surveillance attentive du patient en unité de soins intensifs est alors impérative en raison du risque de dégradation rapide de l'état respiratoire pouvant nécessiter une intubation et une ventilation assistée [43,47]. Enfin, la consommation d'héroïne a un impact sur le contrôle de l'asthme, ce qui nécessite une prise en charge pluridisciplinaire (médecin généraliste, pneumologue et addictologue) [5].…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Si cette consommation est soupçonnée, une analyse toxicologique des urines pour les opiacés peut confirmer le diagnostic. Une surveillance attentive du patient en unité de soins intensifs est alors impérative en raison du risque de dégradation rapide de l'état respiratoire pouvant nécessiter une intubation et une ventilation assistée [43,47]. Enfin, la consommation d'héroïne a un impact sur le contrôle de l'asthme, ce qui nécessite une prise en charge pluridisciplinaire (médecin généraliste, pneumologue et addictologue) [5].…”
Section: Resultsunclassified
“…Observance du traitement de l'asthme Au cours des maladies chroniques comme l'asthme ou les addictions, la mauvaise observance du traitement est la principale cause d'échec thérapeutique [5,42]. Doshi et al [43] ont montré que, comparativement aux sujets consommant de l'héroïne et/ou de la cocaïne, l'observance thérapeutique était meilleure chez ceux n'en utilisant pas, avec une prise plus fréquente de la corticothérapie inhalée (48,9 % vs. 32,9 % ; p < 0,003) ou systémique (28,6 % vs. 15,3 % ; p < 0,003). De plus, ceux qui en consommaient avaient moins souvent un médecin traitant (50,6 % vs. 68,9 % ; p = 0,007).…”
Section: Opinion Des Usagers D'héroïneunclassified
See 1 more Smart Citation
“…Asthma is amongst the most common long-term health conditions in the UK 1 and represents a significant burden for patients, general practice, emergency medicine and secondary care. Small scale observational studies suggest that people with asthma and opioid use disorder (OUD) experience high rates of acute exacerbations 2 , have more severe symptoms during acute episodes 3,4 and are more likely to need intensive care treatment and intubation 5,6 . The UK has one of the highest rates of death from asthma in Europe 7 and in the 2014 UK National Review of Asthma Deaths, substance misuse was identified as a factor in 6% of the cases 8 .…”
Section: Introductionmentioning
confidence: 99%
“…More generally, it is recognised that the literature on the pulmonary consequences of heroin use is scant 18 . When assessing asthma outcomes amongst people with OUD, it is important to acknowledge this group are more likely to be male, come from areas of high deprivation and have smoking histories 5 . Factors such as these have been shown to influence asthma outcomes including exacerbation rates [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%